Simultaneous Measurement of Intracellular pH and K+ or NO3- in Barley Root Cells Using Triple-Barreled, Ion-Selective Microelectrodes. - Walker, D. J. (1995)
The manufacture and use of triple-barreled microelectrodes, which are capable of simultaneous in vivo measurement of intracellular pH and the activities of K+ or NO3- and cell membrane potential (Em), are described. Scanning electron micrographs showed that the three tips were aligned and that the overall tip diameter was approximately 0.8 [mu]m. When filled with 100 mM KCl, all three barrels simultaneously reported identical transmembrane potentials, showing that all three tips were located in the same subcellular compartment. Intracellular estimates of Em in barley (Hordeum vulgare L. cv Klaxon) root epidermal cells obtained with these triple-barreled microelectrodes were indistinguishable from those obtained using single- or double-barreled microelectrodes. Measurements made with triple-barreled K+ and pH-selective microelectrodes in root cells of 7-d-old barley plants grown in a nutrient solution containing 0.5 mM K+ yielded cytosolic and vacuolar populations having mean K+ activity values of 71.3 and 68.7 mM, respectively. The associated mean pH values ([plus or minus]SE) were 7.26 [plus or minus] 0.06 (cytosol) and 5.18 [plus or minus] 0.08 (vacuole). Analysis of whole-tissue digests confirmed the microelectrode measurements. Measurements made using triple-barreled pH- and nitrate-selective microelectrodes confirmed earlier double-barreled measurements of pH and nitrate in barley root epidermal cells growing in 10 mM nitrate.